(untitled) (Indian Journal of Animal Production and Management, 2024)
This report documents a sudden and fatal case of copulatory breeding trauma in a 7-month old NOD SCID male breeder mouse. While similar injuries in other mouse strains typically result in recovery, the immunocompromised status of NOD SCID mice significantly impairs their healing abilities and heightens their susceptibility to infections. The mouse exhibited acute lethargy, gastrointestinal distress, and penile discharge, leading to death within a few hours. Postmortem examination revealed a significantly distended bladder with hemorrhagic spots, and urine analysis showed numerous motile sperm-like structures. The findings indicate that copulatory trauma was the primary cause of death, emphasizing the need for careful monitoring and preventive measures in breeding management, particularly for immunocompromised strains.